The dynamics of soil organic matter accumulation in Portuguese grassland soils - Teixeira R.; Domingos T.; Costa A.P.S.V.; Oliveira R.; Farropas L.; Calouro F.; Barradas A.; Carneiro J.P. (Sustainable Mediterranean grasslands and their multi-functions, 2008)
Carbon sequestration in LULUCF activities occurs by soil organic matter (SOM) accumulation, which varies with grassland type. We built dynamic models to estimate SOM increases in several rainfed grassland soils in Portugal. We considered Sown biodiverse permanent Grasslands (SG), Fertilized Natural Grasslands (FNG), and Natural Grasslands (NG). These results may then be used to estimate the value of sequestered carbon. We considered for all cases a saturating exponential pattern, even though statistically we cannot always reject the hypothesis of linear increases (which would imply the ecologically unsound result that there is no upper boundary for SOM accumulation). Considering that we start from the same initial SOM level, we show that SG accumulate about twice as much as FNG and seven times as much as NG.
12. Meeting of the Sub-Network on Mediterranean Forage Resources of the FAO-CIHEAM Inter-regional Cooperative Research and Development Network on Pastures and Fodder Crop, 2008/04/09-12, Elvas (Portugal)